Isothermal oxidation behavior of NiCoCrAlY/ZrO2 composite coating on γ-TiAl alloy. (15th June 2018) - Ding, Zheng; Miao, Qiang; Liang, Wenping; Yang, Zhengang; Lin, Hao
Abstract: In this study, a composite NiCoCrAlY/ZrO2 coating was applied to enhance the property of oxidation resistance on the surface of γ -TiAl alloys ultilizing radio frequency magnetron sputtering. The phase formation, microstrure and chemical composition of the coatings were investigated by x-ray diffraction (XRD) and scanning electron microscopy(SEM). The interlayer binding force was analyzed using scratch test. Further, static oxidation test was carried out at 950 °C and the oxidation behavior of the coating was investigated. The results indicated the NiCoCrAlY/ZrO2 coating showed high adhesion strength (critical load > 57.5 N) and the oxidation of the coating obeyed a parabolic law. Above all, the oxidation resistance of the substrate was remarkably enhanced after introducing the NiCoCrAlY/ZrO2 coating. The oxidation resistance enhancement could be attributed to the formation of a protective Al2 O3 scale. Besides, the ceramic layer ZrO2 blocked the infiltration of O atoms during high-temperature oxidation.